The Mediterranean Basin and Southern Europe in a warmer world: what can we learn from the past? - Guiot, Joël; Kaniewski, David (Frontiers in Earth Science, 2015)
Since the late-nineteenth century, surface temperatures have increased worldwide but non-uniformly. The repercussions of this global warming in drylands, such as the Mediterranean, may become a major source of concern in the near future, as such warming is often accompanied by increased droughts, that will severely degrade water supply and quality. History shows that access to water resources has always presented a challenge for societies around the Mediterranean throughout the Holocene (roughly the last 10,000 years). Repeatedly climate shifts seem to have interacted with a range of social, economic and political factors, exacerbating vulnerabilities in the drier regions. We present a reconstruction of the Holocene climate in the Mediterranean Basin using an innovative method based on pollen data and vegetation modeling. The method consists of estimating inputs to the vegetation model so that the model's outputs match as far as possible available pollen data, using a Bayesian framework. This model inversion is particularly suited to deal with increasing dissimilarities between past millennia and the last century, especially due to a direct effect of CO2 on vegetation. The comparison of distant past with the last century shows that the intensity of century-scale precipitation has fallen, amplified by higher temperatures. Resulting changes in evapotranspiration appear to be unparalled over the last 10,000 years. Comparison between the western and eastern Mediterranean precipitation anomalies shows a clear see-saw effect through the last 10,000 years, particularly during dry episodes in the Near and Middle East. As a consequence that the recent climatic change seems to have been unprecedented during the last 10,000 years in the Mediterranean Basin, over the next few decades, Mediterranean societies are likely to be more critically vulnerable to climate change than in any previous dry period. We show also that adverse climate shifts are often correlated with the decline or collapse of Mediterranean civilisations, particularly in the eastern Basin.